Incorporation of five common hypnotics into hair after a single dose and application to a forensic case of drug facilitated crimes. (August 2021) - Sasaki, Keiko; Shima, Noriaki; Kamata, Tooru; Ishikawa, Akari; Nitta, Atsushi; Wada, Misato; Nakano-Fujii, Shihoko; Kakehashi, Hidenao; Sato, Takako; Katagi, Munehiro
Highlights: Quantitative hair analysis of triazolam, etizolam, flunitrazepam, nitrazepam and zolpidem after single doses was performed. The incorporation ratios against the dose exhibit similarity between the four benzodiazepines. Zolpidem is more likely to incorporate into hair than benzodiazepines. Abstract: In order to obtain fundamental information on the disposition of hypnotics into hair after a single oral dose the quantitative hair analysis of triazolam (TZ), etizolam (EZ), flunitrazepam (FNZ), nitrazepam (NZ) and zolpidem (ZP) have been performed using a validated LC-MS/MS procedure. Hair specimens (straight, black) were collected from three subjects about one month and three months after a single 0.25 mg dose of TZ, 1 mg of EZ, 2 mg of FNZ, 5 mg of NZ and 10 mg of ZP tartrate. The subjects ingested just one out of five different hypnotics on each day, each of five days in turn. All ingested hypnotics have been detected in hair from each subject both one month and three months after intake, and their concentrations were in the range of 0.023–0.043 pg/hair strand (0.077–0.36 pg/mg) for TZ, 0.11–0.63 pg/hair strand (0.44–5.2 pg/mg) for EZ, 0.14–2.6 pg/hair strand (0.56–22 pg/mg) for FNZ, 0.33–1.7 pg/hair strand (1.3–17 pg/mg) for NZ and 20–40 pg/hair strand (120–270 pg/mg) for ZP. For FNZ and NZ, not only the parent drugs but also their metabolites, 7-amino-FNZ and 7-amino-NZ, were detected in the range of 2.3–9.2 pg/hair strand (9.2–82 pg/mg) and 2.4–9.1 pg/hair strand (8.0–55 pg/mg), respectively. The calculated incorporation ratios into hair against the dose were found to exhibit similarity between the four benzodiazepines. This finding suggests the ability to apply these quantitative data to approximately estimating the amounts of other benzodiazepines, which have similar chemical structures, in hair although it should be noted that the amounts of drugs in hair varies considerably depending on the hair color. On the other hand, the incorporation ratio of ZP showed 15–29 times higher than that of TZ, indicating that lipophilic ZP was more likely to incorporate into hair than benzodiazepines. In addition, the application of the present data to a drug-facilitated sexual assault was shown.